Leadership in Action : Issues and Observations--Deference is an Undervalued Aspect of leadership - Sarcone, Joe (Center for Creative Leadership, 2008)
The fact of limited resources will continue to present leadership challenges. By applying deference-and extending trust, exercising flexibility, and offering patience-leaders can become more effective at dealing with this problem.